2022
DOI: 10.3389/fphar.2022.847905
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin Therapy Improves Cholangiocarcinoma Outcomes by Regulating ERK/Mitochondrial Pathway

Abstract: Background: Silibinin is widely utilized drug in various cancer treatments, though its application in cholangiocarcinoma has not yet been explored. For the first time, we evaluated the anticancer potential and underlying molecular mechanism of silibinin in treatment of cholangiocarcinoma treatment.Methods: HuCCT-1 and CCLP-1 cells were chosen to be an in vitro study model and were exposed to various concentrations of silibinin for indicated times. Cell viability was evaluated by the cell counting kit-8 (CCK-8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The decreased mitochondrial membrane potential is observed before early apoptosis and is widely considered a critical marker of early apoptosis [ 49 ]. Previous studies have shown that reducing mitochondrial membrane potential can induce tumor cell apoptosis, and thus delay tumor cell growth [ 50 ]. In this study, we found that after treatment with Mito-LND, mitochondrial membrane potential decreased, and Caspase-3/7 activity increased in GBM cells, ultimately leading to cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased mitochondrial membrane potential is observed before early apoptosis and is widely considered a critical marker of early apoptosis [ 49 ]. Previous studies have shown that reducing mitochondrial membrane potential can induce tumor cell apoptosis, and thus delay tumor cell growth [ 50 ]. In this study, we found that after treatment with Mito-LND, mitochondrial membrane potential decreased, and Caspase-3/7 activity increased in GBM cells, ultimately leading to cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular carcinoma, silibinin has been found to effectively abate hepatocarcinogenesis and hepatocellular carcinoma growth by regulating various signaling pathways including HGF/c-Met, Wnt/β-catenin and PI3K/Akt/ mTOR (Yassin et al, 2022). In cholangiocarcinoma, silibinin has the ability to inhibit cholangiocarcinoma through the ERK/ mitochondrial apoptotic pathway, which makes silibinin a potential anti-tumor drug candidate for cholangiocarcinoma treatment (Bai et al, 2022).…”
Section: Silibininmentioning
confidence: 99%